How to Report: Knee MRI - Griffith, James Francis (Seminars in Musculoskeletal Radiology, 2021)
The knee is the most commonly examined joint with magnetic resonance imaging (MRI) and, as such, it is the joint that most trainee radiologists start reporting. This article addresses the main pathologies encountered on MRI examination of the knee, outlining the key features to note and report, as well as providing examples of terminology used to describe these findings.
Keywords: knee; magnetic resonance imaging; reporting; cartilage; meniscus